Cationic UV (ultraviolet) photocuring adhesive composition, polaroid and preparation method

Through the use of polarizer manufacturing, the cation UV -optical continuous agent composition is used to solve the problem of the traditional continuous agent that requires oxygen resistance and insufficient heat resistance, and achieve efficient solidification and performance improvement, which meets environmental requirements.

CN119351020APending Publication Date: 2025-01-24KUNSHAN ZHIQIMEI MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411689320.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing UV photocuring ads need oxygen barrier in polarizer manufacturing, and their heat and moisture resistance are insufficient, making it difficult to meet the strict requirements of electronic products for polarizer performance.

Method used

A cationic UV optical solidification follow -up agent composition includes the composition of oxygen -containing group resin prefabricated, multi -official group ring oxygen monomer, diluted monomer, and cationic light induction agent. High -efficiency solidification and no need for oxygen blocking.

Benefits of technology

The follow -up composition achieves high -efficiency solidification under anaerobic resistance, significantly improves the heat resistance and humidity resistance of polarizers, improves production efficiency, and reduces carbon emissions, which meets environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351020A_ABST
    Figure CN119351020A_ABST
Patent Text Reader

Abstract

The invention relates to a cationic UV photocuring adhesive composition which comprises the following components: an epoxy group-containing resin prepolymer, a polyfunctional group epoxy monomer, a diluting monomer, a cationic photoinitiator, a silane coupling agent and an antistatic agent. Wherein the weight-average molecular weight of the epoxy group-containing resin prepolymer is 25000, the Tg is-50 DEG C to-45 DEG C, the PDI is greater than 3, and the epoxy value is 0.5. The main bonding component of the epoxy-group-containing resin prepolymer is prepared through the ring-opening reaction of the cationic initiator, and the molecular weight is large. The adhesive is excellent in performance in the preparation of the polaroid, and can be cured without firstly attaching a release film and performing ultraviolet irradiation in a nitrogen atmosphere, so that the problems of yellowing and the like are avoided, and the production efficiency is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polarizers, and in particular to a cationic UV light-curing adhesive composition, a polarizer, and a preparation method thereof. Background Art

[0002] In the continuous development of polarizer manufacturing technology, adhesive is a key material, and its performance is directly related to the overall quality and processing efficiency of polarizers. For a long time, the market has generally used acrylic resin adhesives, which are thermosetting. Although widely used, they are facing increasingly stringent environmental standards and their limitations are gradually emerging. For this reason, the industry has begun to explore and apply UV-curable free radical reactive acrylic adhesives, such as the technical solution disclosed in patent No. CN 107573893A, which effectively improves production efficiency and reduces environmental pollution through ultraviolet curing.

[0003] However, although UV light-curing free radical reaction adhesives have made breakthroughs in environmental protection and efficiency, the problem of oxygen barrier still needs to be considered in the curing process. The schematic diagram of the process of preparing polarizers with traditional UV light-curing adhesive compositions is shown in the figure. Figure 2 As shown, to ensure the curing quality. At the same time, with the continuous advancement of electronic product technology, the requirements for polarizers in terms of heat resistance and moisture resistance are becoming increasingly stringent. In view of this, although the existing technology has made certain progress, there is still a clear need for improvement. Summary of the invention

[0004] The purpose of the present application is to provide a new adhesive composition, which, when applied to a polarizer, can achieve efficient curing without oxygen barrier conditions, while significantly improving the heat resistance and moisture resistance of the polarizer.

[0005] To solve the above technical problems, the present application can be implemented through the following technical solutions:

[0006] The present application provides a cationic UV light-curing adhesive composition, which comprises the following components in parts by weight:

[0007]

[0008] The weight average molecular weight of the epoxy group-containing resin prepolymer is 25,000, Tg is -50°C to -45°C, PDI>3, and epoxy value is 0.5.

[0009] As a further improvement of the present application, the epoxy group-containing resin prepolymer is prepared from a monomer having the following structural formula:

[0010]

[0011] As a further improvement of the present application, the epoxy group-containing resin prepolymer is composed of several of the following structural formulas connected in series:

[0012]

[0013] As a further improvement of the present application, the epoxy group-containing resin prepolymer is selected from XG01 or XG02 synthesized in East Asia.

[0014] In an optional embodiment, the multifunctional epoxy monomer is a monomer containing multiple double bonds and more than two functional groups.

[0015] As a further improvement of the present application, the diluent monomer is at least one of allyl glycidyl ether, butyl glycidyl ether, 1,4-butanediol diglycidyl ether, alkylene glycidyl ether, ethylene glycol diglycidyl ether, phenyl glycidyl ether, polypropylene glycol diglycidyl ether, C12-14 fatty glycidyl ether, benzyl glycidyl ether, 1,6-hexanediol diglycidyl ether, o-tolyl glycidyl ether, neopentyl glycol diglycidyl ether, oxetane and oxetane derivatives.

[0016] As a further improvement of the present application, the cationic photoinitiator is at least one of a diazonium salt, a diaryl iodonium salt, a triaryl sulfonium salt, an alkyl sulfonium salt, an iron arene salt, a sulfonyloxy ketone and a triaryl siloxane ether.

[0017] To achieve the above object, the present application also provides a polarizer, which is prepared from the cationic UV light-curing adhesive composition described above.

[0018] To achieve the above object, the present application also provides a method for preparing the polarizer described above, comprising the following steps:

[0019] S1, unwinding the PVA original film at the first unwinding position, and sequentially performing swelling, dyeing, bridging, stretching, washing, fixing and drying processes to obtain a PVA polarizer, wherein the PVA polarizer comprises an upper surface and a lower surface opposite to each other, and an upper protective layer and a lower protective layer are arranged adjacent to the upper surface and the lower surface of the PVA polarizer;

[0020] S2, unwinding a release film at a second unwinding position, wherein the release film comprises an upper surface and a lower surface opposite to each other, coating the upper surface of the release film with a cationic UV light-curing adhesive composition, and after ultraviolet irradiation, laminating the upper surface of the release film to the lower protective layer to obtain a semi-finished polarizer;

[0021] S3, unwinding the semi-finished polarizer on the cutting line, cutting and edge grinding, and obtaining a finished polarizer.

[0022] As a further improvement of the present application, in step S2, the energy of the ultraviolet irradiation is greater than 1000 mJ / cm 2 .

[0023] As a further improvement of the present application, the thickness of the cationic UV light-curing adhesive composition after curing is 10 μm to 30 μm, and the surface resistance is less than 9.9×10 11 Ω / cm.

[0024] The beneficial effects of the present application are as follows: The present application provides an innovative cationic UV light-curing adhesive composition, the main adhesive component of which contains epoxy group resin prepolymer, which is prepared by cationic initiator ring-opening reaction and has a large molecular weight. This adhesive performs well in the preparation of polarizers, and can be cured without first attaching a release film and irradiating with ultraviolet light in a nitrogen atmosphere, avoiding problems such as yellowing, and significantly improving production efficiency.

[0025] More importantly, the adhesive composition does not contain solvents, effectively reducing carbon emissions, meeting environmental protection requirements, and embodying the concept of green production. Its excellent performance makes this technical solution have broad application prospects and promotion value in the field of polarizer preparation, which can not only improve product quality, but also reduce production costs and be environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The schematic diagram is a process for preparing a polarizer from the cationic UV light-curing adhesive composition of the present application;

[0027] Figure 2 A schematic diagram of a process for preparing a polarizer from a conventional UV light-curing adhesive composition;

[0028] Figure 3 It is a schematic diagram of the structure of preparing a polarizer from the cationic UV light-curing adhesive composition of the present application. DETAILED DESCRIPTION

[0029] The present application will be described in detail below in conjunction with the various embodiments shown in the accompanying drawings. However, these embodiments do not limit the present application, and any structural, methodological, or functional changes made by a person of ordinary skill in the art based on these embodiments are all included in the protection scope of the present application.

[0030] When the existing UV light-curing free radical reaction type adhesive is prepared into a polarizer, oxygen barrier is required. In order to solve the problem of efficient curing of the adhesive while the polarizer has excellent weather resistance, the present application provides a cationic UV light-curing adhesive composition, which includes the following components by weight:

[0031]

[0032] The weight average molecular weight of the epoxy group-containing resin prepolymer is 25,000, Tg is -50°C to -45°C, PDI>3, and epoxy value is 0.5.

[0033] In an optional embodiment, the epoxy group-containing resin prepolymer is prepared from a monomer having the following structural formula:

[0034]

[0035] In an optional embodiment, the epoxy group-containing resin prepolymer is composed of several of the following structural formulas connected in series:

[0036]

[0037] In an optional embodiment, the epoxy group-containing resin prepolymer is selected from XG01 or XG02 synthesized in East Asia.

[0038] In an optional embodiment, the multifunctional epoxy monomer is a monomer containing multiple double bonds and difunctional groups or more. In addition, high Tg monomers can assist in adjusting the hardness, elastic modulus and other properties of the adhesive composition.

[0039] In an optional embodiment, the diluent monomer is at least one of allyl glycidyl ether, butyl glycidyl ether, 1,4-butanediol diglycidyl ether, alkylene glycidyl ether, ethylene glycol diglycidyl ether, phenyl glycidyl ether, polypropylene glycol diglycidyl ether, C12-14 fatty glycidyl ether, benzyl glycidyl ether, 1,6-hexanediol diglycidyl ether, o-tolyl glycidyl ether, neopentyl glycol diglycidyl ether, oxetane and oxetane derivatives.

[0040] In an optional embodiment, the cationic photoinitiator is at least one of a diazonium salt, a diaryliodonium salt, a triarylsulfonium salt, an alkylsulfonium salt, an iron arene salt, a sulfonyloxy ketone and a triarylsiloxane ether.

[0041] In an optional embodiment, the antistatic agent may be, but is not limited to, commercially available 3M FC4400 and the like, and the silane coupling agent may be, but is not limited to, KBM-403 and the like.

[0042] The present application also provides a polarizer prepared from the above-mentioned cationic UV light-curing adhesive composition.

[0043] In an optional embodiment, the present application also provides a method for preparing a polarizer, such as Figure 1 As shown, the following steps are included:

[0044] S1, unwinding the PVA original film at the first unwinding position, and sequentially performing swelling, dyeing, bridging, stretching, washing, fixing and drying processes to obtain a PVA polarizer, wherein the PVA polarizer comprises an upper surface and a lower surface opposite to each other, and an upper protective layer and a lower protective layer are arranged adjacent to the upper surface and the lower surface of the PVA polarizer;

[0045] S2, unwinding a release film at a second unwinding position, wherein the release film comprises an upper surface and a lower surface opposite to each other, coating the upper surface of the release film with a cationic UV light-curing adhesive composition, and after ultraviolet irradiation, laminating the upper surface of the release film to the lower protective layer to obtain a semi-finished polarizer;

[0046] S3, unwinding the semi-finished polarizer on the cutting line, cutting and edge grinding, and obtaining a finished polarizer, wherein: the structural schematic diagram of the finished polarizer is as follows Figure 3 shown.

[0047] In an optional embodiment, in step S2, the energy of the ultraviolet irradiation is greater than 1000 mJ / cm 2 .

[0048] In an optional embodiment, the cationic UV light-curing adhesive composition has a thickness of 10 μm to 30 μm after curing and a surface resistance of less than 9.9×10 11 Ω / cm.

[0049] In an optional embodiment, the upper protective layer is selected from any of TAC, PMMA, and PET films, and the lower protective film is selected from any of TAC, PMMA, COP, SANUQI, etc. Preferably, a surface treatment layer such as AG, HC, AGLR, HCLR, etc. may be provided outside the upper protective layer. The polarizing plate of the present application can be applied to IPS, VA, and OLED displays.

[0050] In this application: PDI is calculated by the ratio of weight average molecular weight (Mw) to number average molecular weight (Mn), that is, PDI = Mw / Mn. Wherein: Weight average molecular weight (Mw): is the average molecular weight of the polymer calculated by mass, reflecting the contribution of different molecular weight components in the polymer chain, and the component with larger molecular weight has a greater impact on Mw. Number average molecular weight (Mn): is the average molecular weight calculated by the number of molecules or the amount of substance, reflecting the quantitative distribution of different molecular weight components in the polymer chain.

[0051] The unit of epoxy value is meq / g, and when the value is 0.5, it means that each gram of epoxy resin (or substance containing epoxy groups) contains 0.5 milliequivalent (meq) of epoxy groups.

[0052] Example 1

[0053] The present embodiment provides a cationic UV light-curing adhesive composition, which includes the following components, by weight: 10 parts of epoxy group-containing resin prepolymer, 1 part of multifunctional epoxy monomer, 10 parts of diluent monomer, 0.001 parts of cationic photoinitiator, 1 part of silane coupling agent, and 1 part of antistatic agent.

[0054] The epoxy group-containing resin prepolymer is XG01 produced by East Asia Synthetics, the molecular weight of the epoxy group-containing resin prepolymer is 25,000, Tg is -45°C, PDI>3, and the epoxy value is 0.5. The multifunctional epoxy monomer is bisphenol A diglycidyl ether, the diluent monomer is allyl glycidyl ether, the cationic photoinitiator is diaryliodonium salt, the silane coupling agent is Japan Shin-Etsu KBM-403, and the antistatic agent is 3M Company's FC-4400.

[0055] The present embodiment also provides a method for preparing a cationic UV light-curing adhesive composition, firstly, the epoxy group-containing resin prepolymer and the multifunctional epoxy monomer are fully mixed to obtain a first mixed solution, then a diluted monomer is taken, a silane coupling agent and an antistatic agent are added to the diluted monomer in sequence, and the mixture is stirred and fully mixed, and then the first mixed solution is added, and then a cationic photoinitiator is added, and the mixture is fully stirred and mixed again, and the cationic UV light-curing adhesive composition is obtained after defoaming for standby use.

[0056] Example 2

[0057] The present embodiment provides a cationic UV light-curing adhesive composition, which includes the following components, by weight: 70 parts of epoxy group-containing resin prepolymer, 10 parts of multifunctional epoxy monomer, 50 parts of diluent monomer, 0.05 parts of cationic photoinitiator, 5 parts of silane coupling agent, and 5 parts of antistatic agent.

[0058] The epoxy group-containing resin prepolymer is XG01 produced by East Asia Synthetics, the molecular weight of the epoxy group-containing resin prepolymer is 25,000, Tg is -45°C, PDI>3, and the epoxy value is 0.5. The multifunctional epoxy monomer is bisphenol A diglycidyl ether, the diluent monomer is allyl glycidyl ether, the cationic photoinitiator is diaryliodonium salt, the silane coupling agent is Japan Shin-Etsu KBM-403, and the antistatic agent is 3M Company's FC-4400.

[0059] The present embodiment also provides a method for preparing a cationic UV light-curing adhesive composition, firstly, the epoxy group-containing resin prepolymer and the multifunctional epoxy monomer are fully mixed to obtain a first mixed solution, then a diluted monomer is taken, a silane coupling agent and an antistatic agent are added to the diluted monomer in sequence, and the mixture is stirred and fully mixed, and then the first mixed solution is added, and then a cationic photoinitiator is added, and the mixture is fully stirred and mixed again, and the cationic UV light-curing adhesive composition is obtained after defoaming for standby use.

[0060] Example 3

[0061] The present embodiment provides a cationic UV light-curing adhesive composition, which includes the following components, by weight: 40 parts of epoxy group-containing resin prepolymer, 6 parts of multifunctional epoxy monomer, 30 parts of diluent monomer, 0.025 parts of cationic photoinitiator, 3 parts of silane coupling agent, and 3 parts of antistatic agent.

[0062] The epoxy group-containing resin prepolymer is XG01 produced by East Asia Synthetics, the molecular weight of the epoxy group-containing resin prepolymer is 25,000, Tg is -45°C, PDI>3, and the epoxy value is 0.5. The multifunctional epoxy monomer is bisphenol A diglycidyl ether, the diluent monomer is allyl glycidyl ether, the cationic photoinitiator is diaryliodonium salt, the silane coupling agent is Japan Shin-Etsu KBM-403, and the antistatic agent is 3M Company's FC-4400.

[0063] The present embodiment also provides a method for preparing a cationic UV light-curing adhesive composition, firstly, the epoxy group-containing resin prepolymer and the multifunctional epoxy monomer are fully mixed to obtain a first mixed solution, then a diluted monomer is taken, a silane coupling agent and an antistatic agent are added to the diluted monomer in sequence, and the mixture is stirred and fully mixed, and then the first mixed solution is added, and then a cationic photoinitiator is added, and the mixture is fully stirred and mixed again, and the cationic UV light-curing adhesive composition is obtained after defoaming for standby use.

[0064] Example 4

[0065] The present embodiment provides a cationic UV light-curing adhesive composition, which includes the following components, by weight: 40 parts of epoxy group-containing resin prepolymer, 6 parts of multifunctional epoxy monomer, 30 parts of diluent monomer, 0.025 parts of cationic photoinitiator, 3 parts of silane coupling agent, and 3 parts of antistatic agent.

[0066] Wherein: the epoxy group-containing resin prepolymer is XG02 produced by East Asia Synthesis, the molecular weight of the epoxy group-containing resin prepolymer is 25000, Tg is -50°C, PDI>3, and the epoxy value is 0.5. The multifunctional epoxy monomer is bisphenol A diglycidyl ether, the diluent monomer is acryl glycidyl ether, the cationic photoinitiator is diaryl iodonium salt, the silane coupling agent is Japan Shin-Etsu KBM-403, and the antistatic agent is 3M Company's FC-4400.

[0067] The present embodiment also provides a method for preparing a cationic UV light-curing adhesive composition, firstly, the epoxy group-containing resin prepolymer and the multifunctional epoxy monomer are fully mixed to obtain a first mixed solution, then a diluted monomer is taken, a silane coupling agent and an antistatic agent are added to the diluted monomer in sequence, and the mixture is stirred and fully mixed, and then the first mixed solution is added, and then a cationic photoinitiator is added, and the mixture is fully stirred and mixed again, and the cationic UV light-curing adhesive composition is obtained after defoaming for standby use.

[0068] Example 5

[0069] This embodiment provides a method for preparing a polarizer, characterized in that it includes the following steps:

[0070] S1, unwinding the PVA original film at the first unwinding position, and sequentially performing swelling, dyeing, bridging, stretching, washing, fixing and drying processes to obtain a PVA polarizer, wherein the PVA polarizer comprises an upper surface and a lower surface opposite to each other, and an upper protective layer and a lower protective layer are arranged adjacent to the upper surface and the lower surface of the PVA polarizer;

[0071] S2, unwinding a release film at a second unwinding location, wherein the release film comprises an upper surface and a lower surface opposite to each other, coating the upper surface of the release film with any one of the cationic UV light-curing adhesive compositions of Examples 1-4, and after ultraviolet irradiation, the energy of the ultraviolet irradiation is greater than 1000 mJ / cm 2 , laminating the upper surface of the release film to the lower protective layer to obtain a semi-finished polarizer; wherein: the thickness of the cationic UV light-curing adhesive composition after curing is 10 μm to 30 μm, and the surface resistance is less than 9.9×1011Ω / cm;

[0072] S3, unwinding the semi-finished polarizer on the cutting line, cutting and edge grinding, and obtaining a finished polarizer.

[0073] Comparative Example 1

[0074] This comparative example provides a UV light-curing adhesive composition, which includes the following components in parts by weight: 55 parts of CN9178NS (molecular weight 72000), 15 parts of pentaerythritol triacrylate, 15 parts of vinyl pyrrolidone, 0.15 parts of 907 photoinitiator, 3.0 parts of KH560 silane coupling agent, 3.0 parts of FC4400 antistatic agent, and 5 parts of ethoxyethoxyethyl acrylate.

[0075] This comparative example also provides a method for preparing a UV light-curing adhesive composition, comprising mixing pentaerythritol triacrylate and vinyl pyrrolidone evenly, adding a silane coupling agent and an antistatic agent, stirring thoroughly, mixing evenly, adding a photoinitiator, stirring until dissolved evenly, and obtaining a mixed solution A.

[0076] Add the mixed solution A into the CN9178NS main agent, stir and mix evenly, and defoam to obtain a finished UV light-curing adhesive composition for standby use.

[0077] Comparative Example 2

[0078] This comparative example provides a UV light-curing adhesive composition, which includes the following components in parts by weight: 70 parts of CN9014NS (molecular weight 40,000), 5 parts of pentaerythritol triacrylate, 5 parts of vinyl pyrrolidone, 0.06 parts of 907 photoinitiator, 3.0 parts of KH560 silane coupling agent, 3.0 parts of FC4400 antistatic agent, and 15 parts of ethoxyethoxyethyl acrylate.

[0079] This comparative example also provides a method for preparing a UV light-curing adhesive composition, comprising mixing pentaerythritol triacrylate and vinyl pyrrolidone evenly, adding a silane coupling agent and an antistatic agent, stirring thoroughly, mixing evenly, adding a photoinitiator, stirring until dissolved evenly, and obtaining a mixed solution A.

[0080] Add the mixed solution A into the CN9014NS main agent, stir and mix evenly, and defoam to obtain a finished UV light-curing adhesive composition for standby use.

[0081] Comparative Example 3

[0082] This comparative example provides a UV light-curing adhesive composition, which includes the following components, by weight: 40 parts of CN9014NS (molecular weight 40,000), 40 parts of pentaerythritol triacrylate, 15 parts of vinyl pyrrolidone, 0.06 parts of 907 photoinitiator, 3.0 parts of KH560 silane coupling agent, 3.0 parts of FC4400 antistatic agent, and 15 parts of ethoxyethoxyethyl acrylate.

[0083] This comparative example also provides a method for preparing a UV light-curing adhesive composition, comprising mixing pentaerythritol triacrylate and vinyl pyrrolidone evenly, adding a silane coupling agent and an antistatic agent, stirring thoroughly, mixing evenly, adding a photoinitiator, stirring until dissolved evenly, and obtaining a mixed solution A.

[0084] Add the mixed solution A into the CN9014NS main agent, stir and mix evenly, and defoam to obtain a finished UV light-curing adhesive composition for standby use.

[0085] The preparation method of the polarizer of Example 5 was used to prepare the UV light-curing adhesive composition prepared by Examples 1-4 and Comparative Examples 1-3 into a polarizer, and the performance of the composition and polarizer of Examples 1-4 and Comparative Examples 1-3 was tested. The test standards are as follows:

[0086] Peeling force test: Take a sample with a width of 25mm and a length of about 150mm, prepare a smooth surface of soda glass, wipe it clean with a dust-free cloth lightly dipped in ethanol, let it stand for 30 minutes, stick the sample on the glass, use a 2kg roller to roll the prepared sample back and forth once at a speed of 300±0.5mm / s, let it stand for 24 hours at a temperature of 23±2℃ and a relative humidity of 50±5%, peel it 180° at a speed of 300mm / min, record the value, and measure the sample three times in parallel.

[0087] Cohesion test: Take a sample with a width of 25mm and a length of about 150mm, prepare a soda glass with a flat surface, wipe it clean with a dust-free cloth lightly dipped in ethanol, let it stand for 30 minutes, stick a sample with an area of ​​25mm×25mm on the glass, use a 2kg roller to roll the prepared sample back and forth three times at a speed of 300±0.5mm / s, fold the other free end of the sample in half and let the adhesive surface self-adhere, and hang a 1kg weight on the free end, place it in an oven at 80℃ and bake it for 1h. After taking the sample out of the oven, let it stand for 15min, record the sliding distance, and measure the sample three times in parallel.

[0088] Weather resistance test: high temperature 80℃, high temperature and humidity 65℃ 95% RH, cold -40℃, hot and cold shock -35~80℃.

[0089] Size shrinkage rate: 1) Take a 340×250mm sodium glass and wipe it clean with a dust-free cloth slightly dipped in ethanol. Let it stand for 30 minutes. There should be no residual stains on the surface. 2) Take a 200×270mm test piece, tear off the release film to be bonded to the glass with tape, and bond the test piece to the glass with a cold laminator. Use a blue pen to draw the length and width to be measured on the four sides of the test piece and measure the average value. 3) Send the test piece to a pressurized degassing machine, 5kg / cm 2, 50℃, 20min,. After 24h of rest, put it into different weather resistance test machines. 4) After the machine test, let it rest at room temperature for 30min and then measure the average size of the test piece. 5) Dimensional shrinkage change: (final average value - initial average value) / (initial average value) × 100%.

[0090] Yellowing index: Jusco V7100 was used to measure the monomer b value.

[0091] Table 1 shows the properties of the compositions of various embodiments and comparative examples and the peeling force, cohesive force and yellowing index of the corresponding polarizers.

[0092]

[0093]

[0094] Table 2 shows the weather resistance test, dimensional shrinkage and resistance value of the polarizers corresponding to each embodiment and comparative example.

[0095]

[0096] From the data analysis of Table 1 and Table 2, it can be seen that the polarizer prepared by the technical solution of the present application will not have poor appearance phenomena such as floating, peeling, bubbles, and line bubbles under tests such as high temperature resistance (80℃ / 1000hrs), high temperature and humidity resistance (65℃ / 95%RH / 1000hrs), hot and cold shock (-35℃~85℃ / 300cycles), and cold resistance (-40℃ / 1000hrs). It has excellent weather resistance, and also has excellent peel force (>g / 25mm), gel fraction (>80%), cohesion (≤0.1mm), and dimensional shrinkage.

[0097] In summary, the component that plays the main bonding role in the technical solution of the present application has a relatively large molecular weight and is prepared by a ring-opening reaction with a cationic initiator. The molecular chains of the main agent are cross-linked to form a network structure.

[0098] It should be pointed out that the above is only used to explain the preferred embodiment of the present application, and is not intended to limit the present application in any form. Therefore, any modifications or changes made to the present application under the same inventive spirit should still be included in the scope of protection intended by the present application.

Claims

1. A cationic UV light-curing adhesive composition, characterized in that: By weight, it includes the following components: The weight average molecular weight of the epoxy group-containing resin prepolymer is 25,000, Tg is -50°C to -45°C, PDI>3, and epoxy value is 0.

5.

2. The cationic UV light-curing adhesive composition according to claim 1, characterized in that: The epoxy group-containing resin prepolymer is prepared from a monomer having the following structural formula:

3. The cationic UV light-curing adhesive composition according to claim 1, characterized in that: The epoxy group-containing resin prepolymer is formed by connecting several of the following structural formulas in series:

4. The cationic UV light-curing adhesive composition according to claim 3, characterized in that: The epoxy group-containing resin prepolymer is selected from XG01 or XG02 synthesized in East Asia.

5. The cationic UV light-curing adhesive composition according to claim 1, characterized in that: The multifunctional epoxy monomer is a monomer containing multiple double bonds and two or more functional groups.

6. The cationic UV light-curing adhesive composition according to claim 1, characterized in that: The diluent monomer is at least one of allyl glycidyl ether, butyl glycidyl ether, 1,4-butanediol diglycidyl ether, alkylene glycidyl ether, ethylene glycol diglycidyl ether, phenyl glycidyl ether, polypropylene glycol diglycidyl ether, C12-14 fatty glycidyl ether, benzyl glycidyl ether, 1,6-hexanediol diglycidyl ether, o-tolyl glycidyl ether, neopentyl glycol diglycidyl ether, oxetane and oxetane derivatives.

7. The cationic UV light-curing adhesive composition according to claim 1, characterized in that: The cationic photoinitiator is at least one of diazonium salts, diaryl iodonium salts, triaryl sulfonium salts, alkyl sulfonium salts, iron arene salts, sulfonyloxy ketones and triaryl siloxane ethers.

8. A polarizer, characterized in that: The polarizer is prepared from the cationic UV light-curing adhesive composition according to any one of claims 1 to 7.

9. A method for preparing the polarizer according to claim 8, characterized in that: The steps include: S1, unwinding the PVA original film at the first unwinding position, and sequentially performing swelling, dyeing, bridging, stretching, washing, fixing and drying processes to obtain a PVA polarizer, wherein the PVA polarizer comprises an upper surface and a lower surface opposite to each other, and an upper protective layer and a lower protective layer are arranged adjacent to the upper surface and the lower surface of the PVA polarizer; S2, unwinding the release film at the second unwinding position, wherein the release film comprises an upper surface and a lower surface opposite to each other, coating the upper surface of the release film with a cationic UV light-curing adhesive composition, and after ultraviolet irradiation, the energy of the ultraviolet irradiation is greater than 1000 mJ / cm 2 , laminating the upper surface of the release film to the lower protective layer to obtain a semi-finished polarizer; S3, unwinding the semi-finished polarizer on the cutting line, cutting and edge grinding, and obtaining a finished polarizer.

10. The method for preparing a polarizer according to claim 8, characterized in that: The cationic UV light-curing adhesive composition has a thickness of 10 μm to 30 μm after curing and a surface resistance of less than 9.9×10 11 Ω / cm.

Citation Information

Patent Citations

  • Polaroid adhesion agent and polaroid

    CN107573893A